Food Crop Land Use Planning in Banggai Regency - Katili, Hidayat (Jurnal Online Pertanian Tropik, 2020)
Land used to plan to be implemented by considering the appropriateness of existing commodity land needs to be managed to provide information about the appropriateness of specific commodity lands for increasing income and regional development. so this research aims to find out what crop commodities are superior and the carrying capacity of land towards food crop agriculture and to direct the allocation of food crop agricultural land in Banggai Regency. The data analysis used the economic approach of the landfill is an analysis of Localization, Specialization, Basis for determination Leading commodities, Land Suitability analysis for land resource potential analysis. The results showed that localization of eight food commodities that spread throughout the study area while the special or typical food crops namely field rice, corn, and cassava as well as bases in this region, namely, field rice and corn 15 districts (65.2%), cassava 13 districts (56.5%). Furthermore, based on the calculation of the carrying capacity of paddy, peanuts and green beans that experienced a "deficit", corn, soybeans, cassava, and sweet potatoes experienced a "surplus" and land suitability ie quite suitable (S2) and marginal appropriate (S3). Then the directions for allocation of paddy rice directed to 4 sub-district (West Toili, Moilong, Batui, Masama); rice field to 4 sub-district (Batui, Pagimana, Bualemo, and Lamala); corn in the 3 sub-district (Nuhon, Simpang Raya and Pagimana); peanut in the 3 sub-district (West Toili, Bunta and North Balantak); kedelei directed (Bualemo District sub-district); cassava is directed towards the sub-district (Bunta, Nuhon and Bualemo); and sweet potatoes in sub-districts (Nuhon, Simpang Raya and Lamala).